RNA helicase DDX5 acts as a critical regulator for survival of neonatal mouse gonocytes. (5th March 2021) - Xia, Qing; Cui, Guizhong; Fan, Ye; Wang, Xiuqin; Hu, Gongcheng; Wang, Lisha; Luo, Xi; Yang, Lele; Cai, Qingqing; Xu, Kaibiao; Guo, Wenjing; Gao, Minghui; et al.
Abstract: Objectives: Mammalian spermatogenesis is a biological process of male gamete formation. Gonocytes are the only precursors of spermatogonial stem cells (SSCs) which develop into mature spermatozoa. DDX5 is one of DEAD‐box RNA helicases and expresses in male germ cells, suggesting that Ddx5 plays important functions during spermatogenesis. Here, we explore the functions of Ddx5 in regulating the specification of gonocytes. Materials and Methods: Germ cell‐specific Ddx5 knockout ( Ddx5 ‐/‐ ) mice were generated. The morphology of testes and epididymides and fertility in both wild‐type and Ddx5 ‐/‐ mice were analysed. Single‐cell RNA sequencing (scRNA‐seq) was used to profile the transcriptome in testes from wild‐type and Ddx5 ‐/‐ mice at postnatal day (P) 2. Dysregulated genes were validated by single‐cell qRT‐PCR and immunofluorescent staining. Results: In male mice, Ddx5 was expressed in germ cells at different stages of development. Germ cell‐specific Ddx5 knockout adult male mice were sterile due to completely devoid of germ cells. Male germ cells gradually disappeared in Ddx5 ‐/‐ mice from E18.5 to P6. Single‐cell transcriptome analysis showed that genes involved in cell cycle and glial cell line‐derived neurotrophic factor (GDNF) pathway were significantly decreased in Ddx5 ‐deficient gonocytes. Notably, Ddx5 ablation impeded the proliferation of gonocytes. Conclusions: Our study reveals the critical roles of Ddx5 in fate determination of gonocytes, offering a novel insight into the pathogenesis of male sterility. Abstract : Under normal physiologic conditions in the neonatal testes, exogenous growth factor GDNF stimulates intracellular signaling through binding to its receptor GFRα1 and RET in cell membranes of the gonocytes. Subsequently, spermatogenesis is believed to initiate shortly after gonocytes give rise to spermatogonia. Spermatogonia could proliferate via mitosis and differentiate to produce spermatocytes. Germ cell‐specific knockout of Ddx5 results in low expression level of GDNF signaling pathway‐related genes (such as receptor Gfra1 and Ret ) in gonocytes. The disruption of spermatogenesis takes place before spermatogonia formation in the testes of Ddx5 konckout mice. Ddx5 deletion leads to a complete lack of germ cells and infertility in male adults.